Role of Viral Infections in Testicular Cancer Etiology: Evidence From a Systematic Review and Meta-Analysis - Garolla, Andrea; Vitagliano, Amerigo; Muscianisi, Francesco; Valente, Umberto; Ghezzi, Marco; Andrisani, Alessandra; Ambrosini, Guido; Foresta, Carlo (Frontiers in Endocrinology, 2019)
The most represented histotype of testicular cancer is the Testicular germ-cell tumor (TGCTs), both seminoma and non.seminoma. The pathogenesis of this cancer is poorly known. A possible causal relationship between viral infections and TGCTs was firstly evoked almost forty years ago and is still a subject of debate. In the recent past, different authors have argued about a possible role of specific viruses in the development of TGCTs including human papillomavirus (HPV), Epstein Barr virus (EBV), cytomegalovirus (CMV), Parvovirus B-19 and human immunodeficiency virus (HIV). The aim of this present review was to summarize, for each virus considered, the available evidence on the impact of viral infections on the risk of developing TGCTs. The review was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We included all observational studies reported in English language evaluating the correlations between viral infections (HPV, CMV, EBV, Parvovirus B19, HIV) and TGCTs. The methodological quality of studies included in the meta-analysis using a modified version of the “Newcastle-Ottawa Scale”. Meta-analyses were conducted using the ‘Generic inverse variance’ method, where a pooled OR was determined from the natural logarithm (LN) of the studies’ individual OR [LN (OR)] and the 95% CI. A total number of twenty studies (on 265,057 patients) were included in the review. Meta-analysis showed an association with TGCTs only for some of explored viruses. In particular, no association was found for HPV, CMV and Parvovirus B-19 infection (p=ns). Conversely, EBV and HIV infections were significantly associated with higher risk of developing TGCTs (OR 7.38, 95% CI 1.89–28.75, p=0.004; OR 1.71, 95% CI 1.51-1.93, p<0.00001). In conclusion, we found adequate evidence supporting an oncogenic effect of HIV and EBV on the human testis. Conversely, available data on HPV and TGCTs risk are conflicting and further studies are needed to draw firm conclusions. Finally, current evidence does not support an effect of CMV and Parvovirus B-19 on testicular carcinogenesis.